41.1: Distinguished Paper: Viewer Preferences for Shadow, Diffuse, Specular, and Emissive Luminance Limits of High Dynamic Range Displays. Issue 1 (1st July 2013) - Daly, Scott; Kunkel, Timo; Sun, Xing; Farrell, Suzanne; Crum, Poppy
Abstract Once HDR displays were developed, a constant question persisted about how much dynamic range is needed for display. If one uses physical scene luminances or human visual system threshold detections to answer this question, the needed ranges are unachievable at exorbitant cost, and likely to remain so for decades. Therefore we designed studies to find the range that is preferred by human observers, and for suprathreshold appearances. Two studies address the diffuse reflective regions, and a third study tested preferences of highlight regions. Test images were specifically designed to test these limits without the perceptual conflicts that usually occur in these types of studies. For the diffuse range, we found displays capable of a dynamic range between 0.1 and 650 cd/m2 match the average preferences. However, to satisfy 90% of the population, a dynamic range from 0.005 to ∼3, 000 cd/m2 is needed. Since a display should be able to produce values brighter than the diffuse white maximum, as in specular highlights and emissive sources, the highlight study concludes that the average preferred maximum luminance for highlight reproduction satisfying 50% of viewers is ∼2, 500 cd/m2. This value increases to marginally over 20, 000 cd/m2 when catering to 90%. Though there is some variability in preferred brightness between certain demographics, the call for a more capable display is still evident, as preferred luminances found in this study exceed even the best of consumer displays today.